2012
DOI: 10.1016/j.expthermflusci.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a liquid drop on a granular medium: Inertia, viscosity and surface tension effects on the drop deformation

Abstract: An experimental study of liquid drop impacts on a granular medium is proposed. Four fluids were used to vary physical properties: pure distilled water, water with glycerol at 2 concentrations 1 : 1 and 1 : 2 v/v and water with Tween 20 at the concentration of 0.1g.l −1 . The drop free fall height was varied to obtain a Weber number (W e) between 10 and 2000. Results showed that obtained crater morphologies highly depend on the impacting drop kinetic energy (E K ). Different behaviours during the drop spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 36 publications
2
81
0
Order By: Relevance
“…Plotting D c versus E reveals a power-law scaling with an exponent of 0:17 ± 0:01 (Fig. 3A), consistent with Nefzaoui and Skurtys's result (20). This scaling is visibly different from the 1/4 power-law scaling associated with the impact craters created by low-speed solid spheres.…”
Section: Results: Morphology Of Impact Craterssupporting
confidence: 74%
See 2 more Smart Citations
“…Plotting D c versus E reveals a power-law scaling with an exponent of 0:17 ± 0:01 (Fig. 3A), consistent with Nefzaoui and Skurtys's result (20). This scaling is visibly different from the 1/4 power-law scaling associated with the impact craters created by low-speed solid spheres.…”
Section: Results: Morphology Of Impact Craterssupporting
confidence: 74%
“…Instead, Katsuragi argued that the power arises from the scaling of the maximal spreading diameter of the impinging drop, which coincidently follows the same 1/4 scaling with E (22). However, a later study by Nefzaoui and Skurtys showed that D c is not equal to the maximal spreading diameter and a different scaling with D c ∼ E 0:18 was found (20). Although covering a larger dynamic range of E, Nefzaoui and Skurtys only investigated the scaling dependence on E and failed to provide a full scaling for D c .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we consider droplets hitting dry soil, which is both wettable and firm enough to maintain its porous structure during the impingement. When droplets have an impact on powder surfaces or granular layers [40][41][42][43][44] , we did not observe bubble formation during the drop impingement. We speculate that if the porous media deform considerably during impact there are low permeability paths for air to escape from beneath the droplet and so it is not trapped.…”
Section: Resultsmentioning
confidence: 70%
“…It is only in the last decade, that drop impact on sand started to draw the attention of physicists, with studies focused on rain showers [12,13] or single drop impact [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%